Model Pembelajaran Contextual Teaching and Learning (CTL) di SD Gmim II Sarongsong - Ester, Kartini; Sakka, Firdha S.; Mamonto, Fidya; Mangolo, Anthonieta E. M.; Bawole, Refina; Mamonto, Sakina (Peneliti.net, 2023)
Use of Contextual Teaching and Learning (CTL) Methods for Grade 1 Students at SD GMIM II SARONGSONG. This research is to expand the teacher's ability to increase motivation and reading learning outcomes for beginning Grade 1 students. The main objective of this research method is first grade students with the subject of the teacher's research and the research object being beginning reading ability, but the method used is Contextual theory. Teaching and Learning (CTL). This theory describes that education, learning and guidance for children must be in students' real world situations. The method used is the observation method, where the observation method is the process of collecting information or data by directly observing and recording events or behavior that occur in a certain environment. From the results of observations, the learning carried out has experienced improvement and progress. The improvements that occur are as follows: 1. Varied learning methods. 2. Students are always actively involved. 3. Students are braver in reading. Contextual Teaching and Learning (CTL) highlights several main problems. One of them is the challenge of integrating real context into the learning process